Історичні причини Куликовської битви - Гаєцький, В.С. (Наука. Релігія. Суспільство, 2012)
Стаття присвячена проблемі визначення історичних причин битви на Куликовім полі. Виконаний аналіз численних історичних джерел для виявлення того, якими бачилися історичні причини цієї події літописцям і як їх оцінили дослідники цього історичного періоду. Проведене дослідження показало, що перемога в Куликовській битві була здобута і завдяки складному політичному маневруванню Московського князя Дмитра Івановича. Статья посвящена проблеме определения исторических причин битвы на Куликовом поле. Вьполнен анализ многочисленных источников для определения того, какими виделись причины этого события летописцам и как их оценили исследователи этого исторического периода. Проведенное исследование показало, что победа в Куликовской битве была достигнута в том числе и благодаря сложному политическому маневрированию Московского князя Дмитрия Ивановича. In the article, Russian strategy in the Battle of Kulikovo is shown. The aim of this paper is to analyze the numerous historical sources in order to determine the location of Russian and Golden Horde troops before the battle, as well as to reconstruct the course of battle. This study showed that significant role in the successful preparation and ultimate victory of Russian troops in the Battle of Kulikovo was played by Moscow Prince Dmitry Ivanovich, who proved himself not only as a strategist and tactician, but also a skilled leader and organizer.